Analisis pusat-pusat pertumbuhan ekonomi di Kabupaten Toba Provinsi Sumatera Utara - Tambun, Laila Hasyim; Andiny, Puti; Nurlina, Nurlina; Chaira, Teuku Muhammad Iqbal; Asnidar, Asnidar (Nur Science Institute, 2024)
This research aims to determine the centers of economic growth, the interaction between the centers of economic growth and the surrounding areas, the position of economic growth and identify economic sectors in Toba Regency. This research uses scalogram and centrality index analysis methods, gravity analysis, Klassen typology analysis, and LQ (Location Quotient) analysis. The results of the research show that five sub-districts have a high hierarchy as growth centers, namely Balige Sub-district, Silaen Sub-district, Uluan Sub-district, Laguboti Sub-district and Ajibata Sub-district. Based on the 2018-2022 average class typology analysis, regencies in North Sumatra Province dominate Quadrant II, namely Fast Developing Regions. There are four basic economic sectors in Toba Regency, including the agricultural, trade, and forestry sectors; provision of minimal accommodation and meals; government administration, defense, and mandatory social security; as well as educational services.